Multimodality Cardiac Imaging in a Patient with Kawasaki Disease and Giant Aneurysms - Ranjini Srinivasan; Rachel Weller; Anjali Chelliah; Andrew J. Einstein (Case Reports in Pediatrics)
Kawasaki disease is a well-known cause of acquired cardiac disease in the pediatric and adult population, most prevalent in Japan but also seen commonly in the United States. In the era of intravenous immunoglobulin (IVIG) treatment, the morbidity associated with this disease has decreased, but it remains a serious illness. Here we present the case of an adolescent, initially diagnosed with Kawasaki disease as an infant, that progressed to giant aneurysm formation and calcification of the coronary arteries. We review his case and the literature, focusing on the integral role of multimodality imaging in managing Kawasaki disease.